"І слово правди і любові" (Шевченкова правда і її християнськість) - Яременко, В.М. (Слово і Час, 2019)
У статті проаналізовано мотив правди-істини у творчості Тараса Шевченка, його унікальність.
Розглянуто поєднання цього мотиву із сучасністю, коли з'явився термін “постправда” й триває
інформаційна війна. Висловлено міркування, що розширюють тлумачення окремих творів
Шевченка. Окреслено словообраз правди в інших письменників ХVІІ – XIX ст. Розглянуто
ставлення поета до правдивості як чесноту. The paper focuses on the motive of truth and its unique representation in the works by Taras
Shevchenko. The topicality of the issue is explained by the needs of its deeper exploration in the
context of present time when the term “post-truth” appeared and informational war is going on. Using
abundant references to Shevchenko’s and biblical texts, the researcher indicates the features that
characterize “truth” in Shevchenko’s works as a basic concept with Christian meaning. In particular,
the word “truth” is often used by the poet with such lexemes as “light”, “love”, “glory”, “power”, “will”
that involve a strong association with God in the Bible. According to the researcher, Shevchenko’s
texts contain obvious and direct indications proving that the poet understood truth as Christ Himself
or His teaching revealed in Gospel explanations.
The analysis provides considerations which may help to interpret Shevchenko’s works or some
fragments in them. In order to show the unequivocal Christian understanding of the category of truth
by Shevchenko the author repeatedly refers to the thoughts of Christian theologians. Shevchenko’s
“truth” is likened to the concept “will” in the sense of personal and social freedom, but even more it
means the Christian freedom of choice for a man and related human efforts and actions. A powerful
motive of sacrifice in Shevchenko’s works testifies that he noticed the essential feature of the Christian
religion which was reflected in the definition of truth. The paper has a comparative nature as it gives
the examples of using the word/concept of truth by Shevchenko’s predecessors. The poet’s attitude
towards truthfulness as a virtue is also considered. Based on the diary entries and correspondence
of Shevchenko, as well as the memories about the poet, the researcher tries to explore how much
this virtue was inherent to him. Shevchenko’s historiosophy is also taken into consideration. The
conclusions explain why Shevchenko filled the concept of truth with the Christian content exactly.